Therapeutic Targeting of Alternative Splicing: A New Frontier in Cancer Treatment - Murphy, Anthony J.; Li, Alex H.; Li, Peichao; Sun, Hong (Frontiers in Oncology, 2022)
The ability for cells to harness alternative splicing enables them to diversify their proteome in order to carry out complex biological functions and adapt to external and internal stimuli. The spliceosome is the multiprotein-RNA complex charged with the intricate task of alternative splicing. Aberrant splicing can arise from abnormal spliceosomes or splicing factors and drive cancer development and progression. This review will provide an overview of the alternative splicing process and aberrant splicing in cancer, with a focus on serine/arginine-rich (SR) proteins and their recently reported roles in cancer development and progression and beyond. Recent mapping of the spliceosome, its associated splicing factors, and their relationship to cancer have opened the door to novel therapeutic approaches that capitalize on the widespread influence of alternative splicing. We conclude by discussing small molecule inhibitors of the spliceosome that have been identified in an evolving era of cancer treatment.